2008
DOI: 10.1111/j.1365-246x.2008.03947.x
|View full text |Cite
|
Sign up to set email alerts
|

Asthenospheric imprints on the lithosphere in Central Mongolia and Southern Siberia from a joint inversion of gravity and seismology (MOBAL experiment)

Abstract: International audienceWe present a joint inversion of gravity and teleseismic data to enlighten the lithospheric structures of the Baikal–Mongolia region, an area characterized by high topographic contrasts, sporadic Cenozoic volcanism, extension and large transcurrent faulting in the vicinity of the Baikal Rift, Central Asia. The study uses a 1000 km long seismic transect that cross-cuts the main tectonic structures from north to south (namely, the Siberian platform, Tunka basin, Hangay Dome and Gobi-Altai be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 68 publications
9
57
0
Order By: Relevance
“…The result shows a prominent low-V anomaly under the Baikal rift zone extending down to 660 km depth and high-V anomalies in the lithosphere under the Siberian Craton. The result is generally consistent with the lithospheric and asthenospheric features revealed by other geophysical studies in this region (e.g., Achauer and Masson, 2002;Gao et al, 2003;Liu and Gao, 2006;Tiberi et al, 2008). The low-V anomaly is interpreted as a mantle upwelling (plume) which has played an important role in the initiation and evolution of the Baikal rift zone and the formation of Cenozoic volcanism in Baikal.…”
Section: A Mantle Plume Under the Baikal Rift Zonesupporting
confidence: 78%
“…The result shows a prominent low-V anomaly under the Baikal rift zone extending down to 660 km depth and high-V anomalies in the lithosphere under the Siberian Craton. The result is generally consistent with the lithospheric and asthenospheric features revealed by other geophysical studies in this region (e.g., Achauer and Masson, 2002;Gao et al, 2003;Liu and Gao, 2006;Tiberi et al, 2008). The low-V anomaly is interpreted as a mantle upwelling (plume) which has played an important role in the initiation and evolution of the Baikal rift zone and the formation of Cenozoic volcanism in Baikal.…”
Section: A Mantle Plume Under the Baikal Rift Zonesupporting
confidence: 78%
“…It was concluded that if these plumes had existed, they would have been robustly resolved by tomography. It should be added that studying the mantle beneath the volcanic areas in Mongolia using the teleseismic tomography scheme of Tiberi et al (2008) did not reveal any feature which could be unambiguously interpreted as a plume. Therefore, we propose that volcanism in this region is caused by a general large-scale heating of the mantle rather than by small-scale separate plumes.…”
Section: Mantle Traces Of Intraplate Volcanismmentioning
confidence: 97%
“…The presence of low-velocity mantle material under the Baikal Basin was discovered in the late 1970's (Logatchev and Zorin, 1987 and references therein) and confirmed by later studies, including teleseismic tomography, which provided better constraints on the position of the plume (Gao et al, 1994(Gao et al, , 2003Zorin et al, 2003;Zorin and Turutanov, 2005;Tiberi et al, 2008). According to the teleseismic data, asthenosphere in the southwestern Baikal region reaches the crustal base in a wedge-shaped upwarp thickening away from the Siberian craton (Tiberi et al, 2008;Mordvinova et al, 2010). The width of the upwarp, in an WeE direction, is estimated to be about 400e500 km from 3D teleseismic tomography and gravity data Tiberi et al, 2008), as well as from the distribution of volcanism (Rasskazov, 1993).…”
Section: Latest Stagementioning
confidence: 84%
“…According to the teleseismic data, asthenosphere in the southwestern Baikal region reaches the crustal base in a wedge-shaped upwarp thickening away from the Siberian craton (Tiberi et al, 2008;Mordvinova et al, 2010). The width of the upwarp, in an WeE direction, is estimated to be about 400e500 km from 3D teleseismic tomography and gravity data Tiberi et al, 2008), as well as from the distribution of volcanism (Rasskazov, 1993). The asthenospheric upwarp maintains increasing NW extension by creating gravity instability .…”
Section: Latest Stagementioning
confidence: 97%